Investigating culture - Delaney, Carol Lowery, 1940- (Chichester, West Sussex ; Malden, MA : Wiley-Blackwell, 2011)
"In its new Second Edition, the innovative and ever-popular Investigating Culture has been updated and revised to incorporate new teacher and student feedback. Carol Delaney and Deborah Kaspin provide an expanded introduction to cultural anthropology that is even more accessible to students. Revised and enhanced new edition that incorporates additional material and classroom feedback Accessible to a wider range of students and educational settings Provides a refreshing alternative to traditional textbooks by challenging students to think in new ways and to apply ideas of culture to their own lives Focuses on the ways that humans orient themselves, e.g., in space and time, according to language, food, the body, and the symbols provided by public myth and ritual Includes chapters that frame the central issues and provide examples from a range of cultures, with selected readings, additional suggested readings, and student exercises"--
"Investigating Culture: An Experiential Introduction to Anthropology proposes an innovative approach to understanding culture as a constructed phenomenon open to investigation of its implicit premises and explicit forms. This exciting book offers a refreshing hands-on alternative to more traditional textbooks by challenging readers to think about culture in new ways and to apply these ideas to their own lives. Investigating Culture teaches students to think like anthropologists by encouraging them to compare their own cultural experiences with that of anthropologists who enter a culture specifically to study it. Approaching the study of culture or cultural anthropology in this way trains students to confront the reflexive nature of anthropology early on and to distance themselves from the inherent flaws of studying the "exotic Other." Investigating Culture is divided into nine chapters that focus on the variety of ways that humans orient themselves --- in space and time, by means of language, the body, the structures of everyday life, and the symbols of religion and public ritual. Each chapter includes an introduction outlining the central issues, selected classic readings, examples from a variety of cultures, suggested additional readings, and a series of exercises designed to make the analysis of culture personally accessible"--
Keywords: Anthropology; SOCIAL SCIENCE / Anthropology / Cultural